VD_FINDINFO HC / 2014 / 381 vom 10. April 2014 - VD Tribunal cantonal (2014)
FRAIS JUDICIAIRES, DÉPENS, SOLIDARITÉ ACTIVE | 150 CO, 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 319 let. a CPC (CH), 319 let. b CPC (CH)